Early treatment with N-acetylcysteine reduces hepatotoxicity in acute acetaminophen poisoning - Ferretti, Serena; Curatola, Antonietta; Chiaretti, Antonio; Graglia, Benedetta; Gatto, Antonio; Capossela, Lavinia; Pansini, Valeria (Acta Biomedica Atenei Parmensis, 2023)
During the outbreak of COVID19 measures taken to contain the spread of the virus have influenced the mental well-being of adults and adolescents. Acetaminophen overdose is the major cause of drug intoxication among children and adolescents. We reported a case of a 15-year- old girl referred to our Emergency Department 3 hours after ingestion of 10 g of paracetamol for suicidal purposes. She promptly started the administration of intravenous N-acetylcysteine (NAC) and the patient was discharged after 5 days of hospitalization in good clinical condition and with neuropsychiatric follow-up. Our case shows that the timing of the intravenous NAC administration is considered the most important factor in the prevention of acetaminophen-induced hepatic failure, despite high serum levels after acetaminophen ingestion.